The 13th sign - Tubb, Kristin O'Donnell (Feiwel and Friends, 2013)
On her thirteenth birthday, Jalen unwittingly brings the twelve signs of the zodiac to life through a mysterious old book, and soon she, her friend Ellie, and Ellie's brother, Brennan, are battling in the streets of New Orleans to defeat the twelve and their little-known companion before time runs out